Impulse oscillometry in evaluation bronchial hyperresponsiveness in patients with persistent allergic rhinitis - Koruga, Dragan Borislav; Baletić, Nenad; Tot Vereš, Kristina; Perić, Aleksandar (Vojnosanitetski pregled, 2020)
Background/Aim. Impulse oscillometry (IOS) is a method for estimating lung function which is used for early detection of bronchial hyperresponsiveness (BHR) and asthma. The aim of the study was to determine the prevalence of BHR, the correlation between spirometry and IOS and sensitivity and specificity of IOS in proving BHR in patients with persistent allergic rhinitis. Methods. The study included 81 patients with allergic rhinitis. From all of them, medical history was taken, allergy testing was done, as well as measurements of parameters of lung function by the IOS and spirometry before and after nonspecific bronchial provocation test with histamin via Aerosol provocative system. Changes of the IOS parameters to fall in FEV1 of 20% were measured and compared with changes in the spirometry parameters. After bronchial challenge test subjects were divided into two groups: the group with BHR (group 1) and that without BHR (group 2). Results. The mean age of participants was 25.7 ± 5.7 years, and 50.5% were men. Out of the total number of subjects with allergy rhinitis, 56 (58.9%) had a positive BPT. After bronchoprovocation an average increase in the group 1 was 88.15% for Rrs5, 111.98% for Fres, and for AX 819.69%. The high degree of correlation between the IOS and spirometry was proven in the group 2, while the whole group 1 had a weak correlation between parameters of these two methods. High sensitivity and low specificity for ​​Rrs5 and Fres compared to FEV1 in diagnosing BHR was proven. Conclusion. The study demonstrated a high prevalence of BHR in the study group of patients with persistent allergic rhinitis, poor correlation in relation to the spirometric measurements in the group with BHR and a high sensitivity and low specificity of IOS for the detection of early changes in the airways.